The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.03.11.435022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitors of the Small Membrane (M) Protein Viroporin Prevent Zika Virus Infection

Abstract: Flaviviruses, including Zika virus (ZIKV), are a significant global health concern, yet no licensed antivirals exist to treat disease. The small M (Membrane) protein plays well-defined roles during viral egress, yet remains within virion membranes following release and maturation. However, it is unclear whether M plays a functional role in this setting. Here, we show that M forms oligomeric membrane-permeabilising channels in vitro, with increased activity at acidic pH and sensitivity to the prototypic channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…The blockage of this putative viroporin could be the mechanism of action of the herein tested adamantanes against ZIKV (Figure 4, Table 1). We found support to this hypothesis in the preliminary work from Brown and collaborators [58]. This research group demonstrated a reduction in ZIKV envelope protein (E) expression in Vero cells upon treatment with the viroporin inhibitor, rimantadine, in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…The blockage of this putative viroporin could be the mechanism of action of the herein tested adamantanes against ZIKV (Figure 4, Table 1). We found support to this hypothesis in the preliminary work from Brown and collaborators [58]. This research group demonstrated a reduction in ZIKV envelope protein (E) expression in Vero cells upon treatment with the viroporin inhibitor, rimantadine, in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…The blockage of this putative viroporin could be the mechanism of action of the herein tested adamantanes against ZIKV (Figure 4, Table 1). We found support to this hypothesis in the preliminary work from Brown and collaborators [58]. This research group demonstrated a reduction in the ZIKV envelope protein (E) expression in Vero cells upon treatment with the viroporin inhibitor, rimantadine, in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, they combined molecular dynamic simulations with biochemical approaches to provide evidence that ZIKV M protein functions as a rimantadine-sensitive viroporin within virion membranes, with a potential role during the entry and uncoating of infectious viral particles. They also used in vivo ZIKV preclinical models to demonstrate that rimantadine reduces viraemia, supporting that M protein channel activity is a relevant physiological target to block ZIKV infection [58].…”
Section: Discussionmentioning
confidence: 92%
“…Our data highlighted a major role for M residue 36 in proper folding of DENV-2 E protein and proapoptotic activity of ApoptoM. There is mounting evidence that small integral M protein is involved in flavivirus morphogenesis and infection processes [19,20,31,33,38]. It is therefore of priority to generate infectious molecular clones derived from RUN-18 and DES-14 to better understand the role of M residue 36 on the pathogenicity of contemporary SWIO DENV-2 strains.…”
Section: Discussionmentioning
confidence: 84%